Prevalence of body image dissatisfaction and associated factors among physical education students - Ferrari,Elisa Pinheiro (2013)
OBJECTIVE: To determine the prevalence of and factors associated with body image dissatisfaction among physical education students enrolled in a public university. METHODS: This study evaluated 236 students and assessed body image perception (silhouette scale), sociodemographic variables (sex, age, parental education, marital status, university course, work, living arrangement, study shift, and income), physical activity level (International Physical Activity Questionnaire - Short Version), dietary habits, tobacco use, excessive intake of alcohol (questions from the tobacco, alcohol and drugs, and nutrition domains of the FANTASTIC instrument), and nutritional status (body mass index [BMI]). Descriptive analysis, the chi-square test, Fisher’s exact test, and crude and adjusted multinomial regression were used. RESULTS: The prevalence of body image dissatisfaction was 69.5%; 44.1% were dissatisfied with excess weight. BMI ≥ 25.0 kg/m² was associated with dissatisfaction with excess weight; factors associated with dissatisfaction with slimness were being male, eating an unhealthy diet, and smoking tobacco. CONCLUSION: Our findings suggest that female college students with a BMI ≥ 25.0 kg/m² are more likely to present dissatisfaction with excess weight. Being male, eating an unhealthy diet, engaging in physical activity for < 739.61 min/week and smoking tobacco were the variables associated with dissatisfaction with thinness.